Geometry and Cenozoic evolution of the Crimean fold-thrust belt from cross-section balancing and kinematic forward modeling - Nakapelyukh, M.; Belskyi, V.; Ratschbacher, L. (Геофизический журнал, 2018)
The Crimean fold-thrust belt comprises the onshore Crimean-dome fold-thrust belt and the offshore Sorokin accretionary wedge, a sub-surface imbricate stack with high oil and gas potential. We combine geomorphological and balanced cross-section analyses with published low-temperature thermo¬chronology and offshore seismic data to constrain both its present geometry and Cenozoic structural evolution. We interpret the Crimean dome as a map-scale, ramp-related antiform above the Main Crimean thrust, the basal detachment to the onshore part of the fold-thrust belt. The Main Crimean thrust separates the continental Scythian plate from the transitional to oceanic Eastern Black-Sea basin and likely reactivates an Upper Triassic–Lower Jurassic passive continental margin structure. The Crimean fold-thrust belt has accommodated ~24 km shortening since the Eocene, with ~12 km contraction each in the thick-skinned Crimean dome and the thin-skinned Sorokin accretionary wedge. The intermediate geometries in the kinematic evolution traced by the kinematic forward model are testable by future hydrocarbon exploration and thermochronologic studies. Крымский складчато-надвижные пояс состоит из Крымского куполообразного складчатого пояса и аккреционного клина Сорокина с высокими перспективами на нефть и газ. Объединены геоморфологический анализ и метод балансировки геологических разрезов, опубликованные низкотемпературные термохронологични данные и данные акваториальных сейсмических профилей для воспроизведения как современной строения, так и кайнозойской структурной эволюции. Интерпретировано Крымский купол как антиформну структуру в масштабе карты, связанной с главным крымским надвижкой (базальным детачментом для горной части складчатого пояса). Главный крымский надвижка отделяет континентальную Скифский плиту от переходной океанической Схидночорноморського бассейна и, вероятно, реактивируется структуру пассивной Континенталь окраины верхнего триаса-нижней юры. Крымский складчато-надвижные пояс претерпел ~ 24 км сокращения, начиная с эоцена, с примерно одинаковым сокращением (~ 12 км) в обоих структурах - Крымском куполе и Сорокинском аккреционного клине. Промежуточные стадии деформации, прослежены кинематической форвард-моделью, является предметом проверки будущими поисками углеводородов и термохронологичнимы исследованиями. Кримський складчасто-насувний пояс складається з Кримського куполоподібного складчастого поясу та акреційного клину Сорокина з високими перспективами на нафту і газ. Поєднано геоморфологічний аналіз і метод балансування геологічних розрізів, опубліковані низькотемпературні термохронологічні дані та дані акваторіальних сейсмічних профілей для відтворення як сучасної будови, так і кайнозойської структурної еволюції. Інтерпретовано Кримський купол як антиформну структуру в масштабі карти, що пов’язана з головним кримським насувом (базальним детачментом для гірської частини складчастого поясу). Головний кримський насув відділяє континентальну Скіфську плиту від перехідної океанічної Східночорноморського басейну і, ймовірно, реактивує структуру пасивної континентальої окраїни верхнього тріасу—нижньої юри. Кримський складчасто-насувний пояс зазнав ~24 км скорочення, починаючи з еоцену, з приблизно однаковим скороченням (~12 км) в обох структурах — Кримському куполі та Сорокинському акреційному клині. Проміжні стадії деформації, прослідковані кінематичною форвард-моделлю, є предметом перевірки майбутніми пошуками вуглеводнів і термохронологічними дослідженнями.